PENENTUAN PREMI POLIS ASURANSI JIWA DWIGUNA DENGAN KASUS JOINT LIFE PADA GENERASI MILENIAL - Rosita, Silvia; Rahmawati.Z, Yulia (Math Educa Journal, 2023)
This study aims to determine the annual joint life premium for millennial couples, based on three categories (age), namely 1) the husband is older than the wife, 2) the husband and wife are the same age and 3) the husband is younger than the wife. This type of research is quantitative research by applying data from married couples at Tamansiswa University, Padang. The study population was a husband/wife pair of Tamansiswa University employees in Padang with the sample chosen being a 1 year age difference in the age of the millennial couple. The application of the joint life insurance model is applied to endowment life insurance. The dual-purpose life insurance model is the insurance that is most in demand in Indonesia because in addition to compensation being paid if the participant dies within n years, participants also receive compensation if they are still alive after n years have ended. The results of the study show that the smaller the age of the millennial spouse, the smaller the annual premium will be with a difference in the age of the millennial couple of 1 year.